Statistical Characteristics and Regional Differences of Raindrop Size Distribution During 6 Typhoon Rainstorms in Shandong - Wang Jun; Zheng Lina; Wang Hong; Liu Chang (应用气象学报)
Based on disdrometers, Doppler radar products and conventional meteorological observation, precipitation characteristics of typhoon rainstorms affecting Shandong from 2018 to 2021 are explored, and evolution characteristics of raindrop size distribution and integral parameters of typhoon raindrops are analyzed. lgNw-Dm distribution shows that microphysical characteristics of different typhoons are different when entering Shandong. Ampil(1810), Rumbia(1818), Bavi(2008) and In-Fa(2106) are more maritime-like, while Yagi(1814) and Lekima(1909) are more continental-like. Microphysical characteristics of these typhoons are quite different after passing different distance and affected by the environment. Microphysical characteristics of Ampil and Bavi at two observation sites in north and south Shandong are similar, and rain drop size distribution (DSD) characteristics of their convective precipitation are maritime. Microphysical characteristics of Yagi are more continental when it enters Shandong. After moving northward, its DSD changes into a typical continental convective precipitation in northwest Shandong. DSD characteristics of Rumbia convective precipitation in Feicheng, Shandong Province are maritime, and change to continental near Guangrao under the influence of cold air, and then changes to maritime type over Laiyang after moving eastward. Microphysical characteristics of convective precipitation change several times. DSD characteristics of convective precipitation before Lekima denaturation are continental type (Lanling and Gaotang), while the spectral characteristics of convective precipitation DSD change to maritime (Linqu and Zhangqiu) during and after denaturation. In the process of In-Fa moving northward, the precipitation weakens obviously, and the microphysical characteristics of convective precipitation change significantly, from maritime in the south to continental in the north. The statistical relationships of various parameters between continental and maritime convective precipitation are different. The μ-λ statistical relation of the quadratic polynomial show that continental (maritime) precipitation generally has smaller (larger) constant terms except for Capricorn Texas, during which continental (maritime) precipitation generally has a slightly larger (slightly smaller) primary term and a smaller (larger) secondary term. However, Z-R relationship is complicated, and there are no significant differences between continental and maritime convective precipitation processes. Large index b is more likely to appear in continental precipitation processes, while small index b is more likely to appear in maritime precipitation processes. In addition, the proportion of equilibrium DSD is low, which can appear in both maritime and continental convective precipitation process, while the transition DSD with high proportion is more in continental convective precipitation processes.